Formulating and redesigning retention policies for millennial at manufacturing industries of Bangladesh - Hassan M.; Islam S.N.; Jambulingam M.; Alam M.N.; Hosen S. (Inderscience Publishers, 2024)
The manufacturing industries of the private sector play a significant role in the overall development of any country. Despite its phenomenal success, private sectors are facing enormous challenges due to the frequent turnover. These turnovers took place due to the absence of job satisfaction, whereas turnover causes massive overt and covert losses. The study reveals that this emerging problem is likely to continue in the future also. Therefore, the objective of the study was to observe the mediating role of job satisfaction on integrated retention strategy for retaining the millennial employees. SPSS and SEM (AMOS) were used to analyse the data. The results show a significant positive relationship with retention, job satisfaction, and millennial retention factors (servant leadership, management initiative, soft HRM, work-life balance). The study concluded by highlighting the recommendations, contributions, limitations, and research directives for future researchers. Copyright 2023 Inderscience Enterprises Ltd.